Extraction of Green Grass Jelly Leaves as An Alternative Biopolymer in Polymer Flooding - Dita Putri Purnama; Anas Hidayat; Muhammad Khairul Afdhol; Fiki Hidayat (Journal of Applied Engineering and Technological Science (JAETS), 2023)
Biopolymer from Green Grass Jelly Leaves attracts attention due to its friendlier environmental profile and cost-effectiveness in providing raw materials. This research aims to explore the potential of biopolymers from Green Grass Jelly Leaves as an alternative to synthetic polymers in an effort to increase oil recovery involving sequential pretreatment, extraction, and characterization stages to obtain essential pectin compounds. This experiment centers on a biopolymer sourced from Green Grass Jelly Leaves, involving sequential steps of pretreatment, extraction, and characterization to obtain essential pectin compounds. Characterization employed scanning electron microscopy (SEM) and Fourier-transform infrared spectroscopy (FTIR). The recorded peak viscosity for Green Grass Jelly Leaves biopolymer was 2.04 cp at 3000 ppm concentration, contrasting with pectin's 1.98 cp viscosity. In comparison, industrial biopolymer Xanthan Gum displayed significantly higher viscosity at 95.01 cp for 3000 ppm concentration. Thermal stability assessment under reservoir conditions (30°C and 60°C) demonstrated that Green Grass Jelly Leaves biopolymer pectin exhibited peak viscosities of 55.29 cP and 51.77 cP at 3000 ppm concentration, respectively. These results show that the comparison between biopolymer and synthetic polymer is not too far and there is an increase in viscosity as the concentration increases, which can increase sweep efficiency.